2017
DOI: 10.1186/s13690-017-0178-8
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of a set of ten functional somatic symptoms from adolescence to middle age

Abstract: Background: Functional somatic symptoms (FSS), or symptoms without a clear medical explanation are a considerable challenge for health care systems. There is no general consensus as to which symptoms should be regarded functional. Few longitudinal studies on the development of FSS exist and these have mainly been based on the assumption that the factorial structure of a FSS scores variable remains invariant over time. When the analysis covers longer periods of the life course, this may be challenged. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…In our previous study, we identified four trajectories of somatic symptoms from the age 16–43 (‘constantly low’, ‘increasing’, ‘decreasing’ and ‘constantly high’ symptom load). 20 In accordance with previous studies, the prevalence of symptoms was higher for women in our studies compared to men, but the development of symptoms was similar among both genders. 20 It is unclear whether there are gender differences in the predictors of symptom trajectories.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our previous study, we identified four trajectories of somatic symptoms from the age 16–43 (‘constantly low’, ‘increasing’, ‘decreasing’ and ‘constantly high’ symptom load). 20 In accordance with previous studies, the prevalence of symptoms was higher for women in our studies compared to men, but the development of symptoms was similar among both genders. 20 It is unclear whether there are gender differences in the predictors of symptom trajectories.…”
Section: Introductionsupporting
confidence: 93%
“… 18 Membership to a long-term high symptoms trajectory group was associated with the children experiencing more stress and negative life events, parenting stress at baseline and the child’s previous health, such as depressive symptoms, but not overprotective parenting style compared to low or decreasing groups. 16–18 Our own two previous studies on somatic symptoms 19 , 20 have covered the life course up to middle age. These studies, however, concentrated on methodology (multiple response trajectory analysis), and did not investigate predictors or outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Pairwise comparisons were performed as needed by Tukey’s test. Segmented regression , shows the lack of difference in the translocation between 5 nm versus 100 nm AuNPs in the developing lungs.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Pairwise comparisons were performed as needed by Tukey's test. Segmented regression 14,15 shows the lack of difference in the translocation between 5 nm versus 100 nm AuNPs in the developing lungs. (Figure 4b; Table S2 in the Supporting Information provides the numerical values of data plotted in Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation